Knowledge of relatives/caregivers about cognitive impairment and dementia - Aponte, Mariel Carolina Montiel [UNIFESP] (2021)
OBJECTIVES: Relatives and caregivers recognize that they receive little information and have poor knowledge about cognitive impairment and dementia. Among general population, the knowledge about cognitive impairment seems to be worse. This study aimed to identify beliefs about aging and cognitive impairment among people who are in contact with older people with and without cognitive impairment, hypothesizing that the fact of being a close relative influences or modifies these beliefs. METHODS: Seventy-eight (78) participants were classified in two groups; group 1: relatives of patients with cognitive impairment or dementia from a behavioral neurology outpatient clinic (n1=48); and group 2: relatives of patients without objective cognitive impairment from different services of a geriatric outpatient clinic (n2=30). All subjects were asked to answer two questionnaires. The first questionnaire was structured by the authors containing demographic and social characteristics and questions about causes and risk factors for dementia, the second questionnaire was the translated version of the Knowledge of Memory Aging Questionnaire of the Louisiana State University. RESULTS: Participants were mainly female and first-degree relatives. No statistical differences were observed for age, education, or follow-up time among the groups. The relatives of patients with cognitive impairment (group 1) showed more self-initiative to look for information about dementia (n1:N1= 31; ̂= 0.65 [0.52 ; 0.78] vs. n2:N2=10; ̂ = 0.33 [0.24 ; 0.42]; p= < 0.01). When asking about sources of information, the three most common answers were Doctors and health professionals (n1:N1= 39; ̂= 0.81 vs. n2:N2= 26; ̂= 0.87; p= 0.49); Internet (n1:N1= 36; ̂= 0.75 vs. n2:N2= 16; ̂= 0.53; p= 0.04), and Journal/books for both groups (n1:N1= 21; ̂= 0.44 vs. n2:N2= 8; ̂= 0.27; p= 0.13). Most of participants recognized Alzheimer’s disease as the main cause of memory loss in older adults (n1:N1= 34; ̂= 0.71 [0.57 ; 0.85] vs. n2:N2=15; ̂ = 0.50 [0.22 ; 0.58]; p= 0.06); other questions about dementia causes and risk factors showed higher scores for participants in group 1, however, no statistical differences were found. Knowledge of Memory Aging Questionnaire of the University of Louisiana: the scores were lower than expected and no statistical differences were found among the groups (group 1: Adjusted score of Normal Memory Questions= 0.61 ± 0.15; Adjusted score of Pathological Memory Questions= xii 0.62 ± 0.14 vs. group 2: Adjusted score of Normal Memory Questions= 0.63 ± 0.16; Adjusted score of Pathological Memory Questions= 0.64 ± 0.12). No statistical correlations were found between the scores and the variables education and disease duration. CONCLUSIONS: Relatives of patients with dementia have more initiative to get informed, the Internet and health professionals are important sources of information. However, dementia knowledge is low even among the people in contact with this syndrome; misconceptions are common about cognitive changes in aging, leading to underestimation of pathological sings. These observations highlight the importance of developing educational strategies for general population and especially for relatives and caregivers, in order to improve the quality of life for patients and their relatives.